Charge‐Scaling Effect in Ionic Liquids from the Charge‐Density Analysis of N, N′‐Dimethylimidazolium Methylsulfate1. Issue 12 (20th February 2014) - Beichel, Witali; Trapp, Nils; Hauf, Christoph; Kohler, Oliver; Eickerling, Georg; Scherer, Wolfgang; Krossing, Ingo
Abstract The charge scaling effect in ionic liquids was explored on the basis of experimental and theoretical charge‐density analyses of [C1MIM][C1SO4] employing the quantum theory of atoms in molecules (QTAIM) approach. Integrated QTAIM charges of the experimental (calculated) charge density of the cation and anion resulted in non‐integer values of ±0.90 (±0.87) e. Efficient charge transfer along the bond paths of the hydrogen bonds between the imidazolium ring and the anion was considered as the origin of these reduced charges. In addition, a detailed QTAIM analysis of the bonding situation in the [C1SO4]− anion revealed the presence of negative πO→σ*S‐O hyperconjugation.